Involving Students in Developing Material in Speaking Class: Students’ Perceptions - Daud Jiwandono (English Education Department - Universitas Nasional Karangturi, 2021)
Speaking skills is important especially for future English teachers since it is the most widely used means of communication used in the teaching and learning process. In order to be able to deliver the material seamlessly, the teachers should have high competence in speaking with other competencies as well. This study aims to identify the students’ speaking circumstances and their perceptions of the involvement of students in developing material in speaking class. This study was a descriptive qualitative study employing observation, questionnaires, and interviews as the means of collecting data. The participants of this study were 7 second-semester students of the English education department at Universitas Nasional Karangturi Semarang joining in a transactional conversation speaking class. Inductive data analysis in this study was based on Burns (2010) and Hatch (2002). The results showed that the majority of the students still find it difficult to find a company in learning speaking from native English, however, it shifted into the native English that wanted to be a conversation buddy with them continuously, not only one-time conversation. The second was that the students were glad to be involved in the material development of the speaking class. Since they have different likings to native English videos to refer to. Introducing a topic at the beginning of the class really helped the students to stay on the right track in searching for the native English video in the speaking class.